Speleogenesis and secondary cave minerals in quartz-sandstone and quartzite environment - Sauro, Francesco <1984> (Alma Mater Studiorum - Università di Bologna, 2014)
The main objective of this research is to improve the comprehension of the processes controlling the formation of caves and karst-like morphologies in quartz-rich lithologies (more than 90% quartz), like quartz-sandstones and metamorphic quartzites. In the scientific community the processes actually most retained to be responsible of these formations are explained in the “Arenisation Theory”. This implies a slow but pervasive dissolution of the quartz grain/mineral boundaries increasing the general porosity until the rock becomes incohesive and can be easily eroded by running waters. The loose sands produced by the weathering processes are then evacuated to the surface through processes of piping due to the infiltration of waters from the fracture network or the bedding planes. To deal with these problems we adopted a multidisciplinary approach through the exploration and the study of several cave systems in different tepuis. The first step was to build a theoretical model of the arenisation process, considering the most recent knowledge about the dissolution kinetics of quartz, the intergranular/grain boundaries diffusion processes, the primary diffusion porosity, in the simplified conditions of an open fracture crossed by a continuous flow of undersatured water. The results of the model were then compared with the world’s widest dataset (more than 150 analyses) of water geochemistry collected till now on the tepui, in superficial and cave settings. All these studies allowed verifying the importance and the effectiveness of the arenisation process that is confirmed to be the main process responsible of the primary formation of these caves and of the karst-like superficial morphologies. The numerical modelling and the field observations allowed evaluating a possible age of the cave systems around 20-30 million of years.